Factors Causing Outpatient Long Waiting Time at Outpatient Polyclinic of X Hospital - Prasetyo Anggun Wicaksono, Achmad Rizki; Vindhya Putri, Aryani; Melani, Asti (Fakultas Kedokteran Universitas Brawijaya, 2024)
The long waiting time at the outpatient polyclinic is challenging at various hospitals. Waiting too long at the outpatient polyclinic will decrease patient satisfaction, so hospitals must continue improving quality service. Therefore, this study aimed to discover the causes of outpatient prolonged waiting time and solutions to these problems. This research was qualitative research conducted at X Hospital in Malang. The research sample was five participants. In this study, direct interviews, FGDs, and questionnaires were used. Factors causing prolonged waiting time for outpatient services at X Hospital that were not yet effective or still exceeded the minimum standard of hospital services were obtained through observation and Focus Group Discussions (FGDs); and the three root causes compiled using a fish diagram were no online registration and online queues, no Standard Operating Procedure regulating delays in the arrival of specialists for outpatient care, and a limited number of human resources. An alternative solution to the root of the problem was the creation of a Standard Operating Procedure that specifically regulates delays in specialist doctors at the outpatient polyclinic, creating WhatsApp online registration, and increasing the number of human resources in the outpatient polyclinic registration desk.